OPTIMALISASI PENDISTRIBUSIAN BARANG MENGGUNAKAN METODE GOAL PROGRAMMING (STUDI KASUS: PT. WULANTIKA UTAMA) - Novrianti, S S; Jaya, A I; Resnawati, Resnawati (Program Studi Matematika, Universitas Tadulako, 2018)
PT.Wulantika Utama is one of distributor in Palu who distribute products from factories to retailers. The purpose of this research are to maximize the distribution numbers of trucks and minimize the cost of distribution. Goal Programming is a method that can solve the problem with more than one purpose. Goal Programming model formulation in this study consists of 5 priority and 5 constraint functions. The fifth priority is the storage capacity, the number of trucks used for the distribution of goods to Donggala, Ampana, Poso, and cost targets are minimum distribution. Constraint function consists of inventory in the warehouse, the number of trucks and distribution costs. The results showed that the supply of goods by the warehouse capacity that can fulfiil the necessary distributionÂ product during a month amounted to 14.755 cartons. Optimal distribution for each destination, in Donggala are 8 trucks with a capacity of 250 cartons, Poso are 20 trucks with a capacity of 300 cartons and Ampana are 14 trucks with a capacity of 500 cartons. This result can save distribution costs of Rp.90.993.009 from the previous distribution costsÂ of Rp. 282 602.689.